Stop-and-go soil fertility measurement by using all terrain vehicle for in-situ nitrate measurement - Mohamed Kassim, Anuar; Yaacob, Mohd Rusdy; Aili, Mohd Faiq Aiman; Subramonian, Sivarao; Awangku Jaya, Awangku Khairul Ridzwan; Ngadiron, Zuraidah; Yasuno, Takashi (International Journal of Agricultural, Forestry & Plantation, 2024)
Agriculture is the main source of food, and it plays an important role in economic growth. The chemical fertilizer that is not absorbed by the plant becomes chemical waste in the soil and flows into underground water, causing water pollution, soil pollution, and acidic rain. The waste of fertilizer in agriculture activities should be minimized to prevent the degradation of the environment. Hence, this project describes the design and development of on-the-go and real-time measurements for soil fertility by using an all-terrain vehicle (ATV). Conventionally, the soil sample needs to be sent to a laboratory for lab analysis, which takes about 2-3 months. Therefore, the device that can measure and analyze soil fertility is a stop-and-go device to determine fertilizer recommendations. The Ion selective electrode (ISE) for nitrate (NO3-) micronutrient with the GPS device will be installed on the ATV device and can be easily changeable. This paper aims to design and develop a soil proximal sensory-based soil collecting system with GPS that can analyze the concentration of the micronutrients contained in the soil and form a fertility mapping. The percentage of error for the sensor will be evaluated before the starting the soil sampling. The soil sample will be done in palm oil field, the depth of the soil collected in 20 cm and 42 samples collected in distance of 10 m between each sample in area of 4 acres. The correlation of the soil sensor and the lab analysis will be done. In the end, the soil mapping and the recommendation map to the farmer based on the result will be developed.